THE PERSONIFICATION OF THE USER’S INTERFACE: CLASSIFICATION VS. CLUSTERIZATION OF USERS OF ONLINE COURSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Researchers compared the classification and the clusterization of users of online course for the personification of the users’ information system interface. When interacting with control and information systems, users may manifest individual features, including implicit characteristics that may affect one’s results within the system. At the same time due to information system building peculiarities one of the most comprehensive statistics can be collected via e-learning systems. When using a course, the user leaves a wide trail of activity that may contain different information depending on the learning environment structure. Online blended learning courses draw the researcher’s attention to the impact of digital teaching models on students as well as its ability to adjust distant learning courses to individual students’ needs and differences. Information personalization is a highly relevant content presentation at the most individual level. Therefore, the task of personalization is to show users information that meets their needs and interests. Personalization gives the opportunity to focus on points that have real value for users.